DEGRADASI MORAL DALAM DUNIA PENDIDIKAN DI SEKOLAHDASARDALAM PERSPEKTIF PEDAGOGIK - Eti Susanti; Robandi, Babang; Halimah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Moral degradation in education, especially at the elementary school level, has become one of the major challenges in shaping a young generation with strong character. This phenomenon is characterized by students' behavior that deviates from social norms, such as a lack of respect for teachers and peers, as well as an increase in deviant behaviors like bullying. From a pedagogical perspective, this moral degradation reflects the failure of character education, which should be a priority in schools. This article aims to examine the causes of moral degradation in elementary schools from a pedagogical point of view and provide solutions to address it. A holistic approach, integration of character education into the curriculum, and the role of teachers as role models are key to overcoming this problem. This study is expected to serve as a foundation for formulating more effective educational policies in shaping the moral character of the younger generation.